Adolescent cultural identity and self-esteem in a multicultural society - Khanlou, Nazilla (My University, 1999)
This study examined the relationship between cultural identity and self-esteem of adolescents living in a multicultural context. The sample of 550 respondents participating in the study came from four secondary schools in the Hamilton-Wentworth Region, located in the Province of Ontario. The study had a cross-sectional design and used the survey method. Multiple instruments were used in the measurement of cultural identity and self-esteem levels. The Current Self-Esteem scale was introduced as an instrument to measure current self-esteem levels and, through its open-ended items, to identify the promoters and challengers of self-esteem, as defined by the respondents. The relationship between cultural identity and self-esteem was found to evolve out of a context that was influenced by the adolescents' individual (age, gender) and environmental (cultural background, acculturating group, family circumstances, perception of support) attributes. In addition, the emerging complex relationship between cultural identity and self-esteem levels was concluded to be influenced by the contextual nature of cultural identity, the multiple influences on self-esteem, and, possibly, the contextual nature of self-esteem as well. The concepts of neighbourhood concordance and global valuation were introduced among the explanations for the emerging patterns of cultural identification. The findings reinforced the thesis' conception of cultural identity as a dynamic, context-dependent process, which, as an aspect of identity, manifests itself in the presence of culturally-different other(s). The use of the term multiculturation was proposed in future conceptual and empirical work on adolescent cultural identity and self-esteem in Canada. As a concept, the term multiculturation recognizes that the development of cultural identity in a multicultural context can follow many paths, which are not limited to specific cultural and migrant groups, thus contributing toward a society which embraces cultural differences and recognizes such differences as a normal part of human development.
Keywords: Nursing; Nursing